Sustainable Development and CSR Practices in an Emerging Economy - Dragos Andrei STOICA (Dunarea de Jos University of Galati, 2021)
With the overthrow of the communist regime in 1989, Romania entered a period of major economic transition. The economic recovery began in the early 2000s, with the opening of options to join NATO and become a member of the EU. Corporate social responsibility is a broad concept that can take many forms depending on the company and industry. Through CSR programs, companies can benefit society while positively developing their brand. As important as CSR is to the community, it is just as valuable to a company. In this article I surveyed actors who hold middle and top management positions in companies present in Romania, and whose entities disclose CSR inputs and outputs separately from their financial statements. The objective of this paper is to give an answer to the research question “Are the CSR policies implemented in Romania enough to ensure a prosperous development of the community?”.